PHYSICAL COMORBIDITIES IN CHILDREN WITH AUTISM SPECTRUM DISORDERS - Ziske Maritska; Rahmi Isman; Bintang Arroyantri Prananjaya; Nita Parisa (Universitas Muhammadiyah Ponorogo, 2022)
Autism Spectrum Disorders (ASD) is a neurodevelopmental disorder characterized by two core symptoms; impairments in social communication and restricted or repetitive behavior. ASD is a broad group of conditions where patients have a variety of abilities and needs. Their ASD related-physical and psychological comorbidities also affect their mortality risk. This study wished to investigate physical comorbidities associated with ASD in the national reference hospital in Indonesia. This is a descriptive study with a cross-sectional approach on children with ASD who visited RSUP Dr. Mohammad Hoesin, Palembang, during 2014-2018. Data were obtained from the medical records and telephone interviews with the parents. Of all the 60 participants included in the study, most are male (n=52;86,7%). The most prevalent ASD-related physical comorbidities were gastrointestinal disorders (n=27;45%), followed by nervous system disorders (n=35;58,3%), and immune system disorders (n=11;18,3%). Despite the small sample size, the prevalence of ASD-related physical comorbidities in children with ASD is profoundly high, implying the need to do early detection from both parents and health professionals to prevent morbidity and complications that may occur. Children with autism can benefit from various therapies start in early childhood and continue throughout their lives to improve their development, and quality of life.